Genotyping of ABCC8, KCNJ11, and HADH in Iranian Infants with Congenital Hyperinsulinism - Hashemian, Somayyeh (Case Rep Endocrinol, 2021)
BACKGROUND: Congenital hyperinsulinism (CHI) is a heterogeneous disease with various underlying genetic causes. Among different genes considered effective in the development of CHI, ABCC8, KCNJ11, and HADH genes are among the important genes, especially in a population with a considerable rate of consanguineous marriage. Mutational analysis of these genes guides clinicians to better treatment and prediction of prognosis for this rare disease. The present study aimed to evaluate genetic variants in ABCC8, KCNJ11, and HADH genes as causative genes for CHI in the Iranian population. METHODS: The present case series took place in Mashhad, Iran, within 11 years. Every child who had a clinical phenotype and confirmatory biochemical tests of CHI enrolled in this study. Variants in ABCC8, KCNJ11, and HADH genes were analyzed by the polymerase chain reaction and sequencing in our patients. RESULTS: Among 20 pediatric patients, 16 of them had variants in ABCC8, KCNJ11, and HADH genes. The mean age of genetic diagnosis was 18.6 days. A homozygous missense (c.2041-21G > A) mutation in the ABCC8 gene was seen in three infants. Other common variants were frameshift variants (c.3438dup) in the ABCC8 gene and a missense variant (c.287-288delinsTG) in the KCNJ11 gene. Most of the variants in our population were still categorized as variants of unknown significance and only 7 pathogenic variants were present. CONCLUSION: Most variants were located in the ABCC8 gene in our population. Because most of the variants in our population are not previously reported, performing further functional studies is warranted.